Association Between White Matter Hyperintensities and Chronic Kidney Disease: A Systematic Review and Meta-Analysis - Wei, Cun-Sheng; Yan, Cai-Yun; Yu, Xiao-Rong; Wang, Lin; Zhang, Rui; Jiang, Jun-Ying; Dai, Qi; Li, Jun-Rong; Chen, Xue Mei (Frontiers in Medicine, 2022)
Objectives Previous studies of the associations between white matter hyperintensities (WMH) and chronic kidney disease (CKD) were still conflicting; therefore, our study aimed to conduct a systematic review of all of the available research on this topic and a meta-analysis of the association between WMH and CKD among observational studies. Setting and Design Systematic review and meta-analysis. Outcome Measures Severity of WMH. Methods and Participants All relevant studies in public databases were examined until 15 November 2020. Two independent reviewers assessed all the included studies using the Cross-Sectional/Prevalence Study Quality (CSSQ) scale, and then literature review and meta-analyses were undertaken. Results We pooled the odds ratio (OR) for the presence of WMH, periventricular hyperintensities (PVH), and deep subcortical white matter hyperintensities (DWMH) of patients with CKD vs. non-CKD patients by subgroup analysis, and the results obtained were WMH OR 2.07, 95% CI [1.58, 2.70], PVH OR 2.41, 95% CI [1.90, 3.05], and DWMH OR 2.11, 95% CI [1.60, 2.80], respectively. The main outcome showed that patients with CKD were more likely to have WMH in the brain compared to the normal controls. Another meta-analysis showed a statistically significant decline in renal function in patients with moderate to severe WMH compared with those with no to mild WMH. Conclusions The findings indicated that patients with CKD were more likely to experience WMH than demographically matched controls. On the other hand, patients with moderate to severe WMH in the brain had poor renal function more frequently than those with no to mild WMH.